Teaching Technique Of Islamic Studies In Higher Learning Institutions For Non-arabic Speakers : experience Of Faculty Of Quranic And Sunah Studies And Tamhidi Centre, Universiti Sains Islam Malaysia - Azniwati Abdul Aziz; Mohammed Akhiruddin Ibrahim; Azlina Mohamed Nor; Mohammad Hikmat Shaker (Horizon Research Publishing Corporation, 2024)
Globalization causes educational institutions to encounter various challenges and demand, in which they need to play their roles in improving competitiveness and world-class quality education. Universiti Sains Islam Malaysia (USIM) as a university that integrates Naqli and Aqli knowledge has taken the globalization challenge by requiring the adoption of English and Arabic language as a teaching and learning medium with adaptability of knowledge discipline even though majority of the lecturer and students are non-speakers of those languages. For Islamic Studies field, the required medium is Arabic language since it is a discipline of al-Naqli knowledge which is based on knowledge in Arabic language where all the basic sources of Islamic studies namely al-Quran, Hadis and Thurath books are in Arabic language. The objective of this article is to study the teaching techniques applied by the non-Arabic speaking lecturers when they carry out teaching and learning process of Islamic studies to non-Arabic speaking students. This research was conducted based on experience of the lecturers of Islamic studies at Faculty of Quranic & Sunnah Studies and Tamhidi Centre, USIM. From the research, it was found that each teaching method such as lecture session, tutorial and e-learning was conducted with different teaching techniques. Various techniques have been applied accordingly such as brainstorming, discussion, presentation, story-telling, role play, Q&A, quiz, forum, and exercises. Result shows that the teaching techniques applied in teaching Islamic studies for non-Arabic speakers are suitable with the ability and basic knowledge of students. Result also found that the techniques used are significance in teaching process for non-Arabic speaking students in higher education level. Since the students of Faculty of Quranic & Sunnah Studies and Tamhidi Centre have basic knowledge in Arabic language and Islamic studies while they were in high school, research suggests on pursuing these teaching techniques and enhancing them from time to time.